Viscous Oil Film Thermal Modeling of Hydrostatic Bearings With a Rectangular Microgroove Surface - Liu, Teng; Li, Chentao; Duan, Runze; Qu, Huiru; Chen, Faze; Zhou, Zhenlin; Zhang, Jianjun; Shi, Zhanqun (Frontiers in Energy Research, 2022)
The thermal effect of viscous oil film of hydrostatic bearings is the key factor causing bearing errors, and the hydrostatic bearing working surface with microgroove structures can potentially inhibit the thermal effect and effectively ensure the bearing accuracy. In this paper, a modeling method for oil film heat generation of hydrostatic bearings with rectangular microgroove working surface is established, and the influence from microgroove design scales onto oil film heat generation is studied. Firstly, the flowing field numerical simulation model of hydrostatic bearing oil film is established, and verified by published analytical model. Based on the simulation method, oil film flowing behaviors of hydrostatic bearing with rectangular microgroove working surface are studied. Then, by combining the analytical calculation of viscous heat generation of hydrostatic oil film and its flowing field simulation, a modified oil film thermal modeling of hydrostatic bearings with rectangular microgroove working surface is established. On this basis, the design scale influence of microgroove onto oil film heat generation is studied. It can be concluded that with the appropriate scales of rectangular microgroove, the working surface with microgrooves can reduce the average velocity of viscous flow field of hydorstatic bearing oil film, and restrain the its energy loss and heat generation.